Organizational commitment and turnover intention in Malaysia: organizational justice as a determinant - Ponnu, C.H.; Chuah, C.C. (2010)
The purpose of this study is to ascertain the importance of employees' justice perception toward their commitment with an organization and their intention to leave the organization. Numerous studies have been carried out in western countries to investigate the effects of perceived equity among employees. However, there are no such studies done in the Malaysian context. Therefore, this study attempts to fill the gap by investigating the relationship between organizational justice, organizational commitment and turnover intention of Malaysian employees. Using a sample of 172, collected from employees across organizations in the country, both procedural and distributive justice perceptions were significant contributors In explaining organizational commitment and turnover intention. Perceptions of organizational justice (procedural justice and distributive) were positively related to organizational commitment but negatively related to employees' turnover intention. Additional analyses revealed that perception of procedural justice was more important to organizational commitment than perceptions of distributive justice. However, perception of distributive justice was more important to turnover intention than perceptions of procedural justice. These findings have important implications for managers in formulating appropriate strategies, policies and procedures to improve employees' commitment to their organizations and to reduce their turnover intentions.